Advances in Tourism Economics New Developments - Matias, Álvaro; Nijkamp, Peter; Sarmento, Manuela (Physica-Verlag HD : Imprint: Physica, 2009)
'Advances in Tourism Economics' follows his predecessor 'Advances in Modern Tourism Research' (2007) in providing a thorough assessment of state-of-the-art economic research in this rapidly developing field. The authors start by analyzing the recent upsurge of model-based economic research in the field, which builds on powerful tools in quantitative economics, such as discrete choice models, social accounting matrices, data envelopment analyses, impact assessment models or partial computable equilibrium models including environmental externalities. The volume originates from this novel research spirit in the area and aims to offer an attractive collection of operational research tools and approaches. It forms an appealing record of modern tourism economics and positions the field within the strong tradition of quantitative economic research, with due attention for both the demand and supply side of the tourism sector, including technological and logistic advances.